Customer satisfaction level through services quality of MARA / Siti Nur Aminah Abdul Razak and Zawiah Mohd Mahidin - Abdul Razak, Siti Nur Aminah; Mohd Mahidin, Zawiah (2014)
This research is conducted to examining the customer satisfaction level through service quality of MARA. A survey on customer satisfaction level through service quality was conducted among customer in MARA Melaka and MARA Muar involved 100 respondents. The attributes of service quality such as tangible, reliability, responsiveness, assurance and empathy have been identified in order to investigate whether or not these factor have significant relationship with customer satisfaction. From this study, the researcher can be able to identify the problem which relay on the level customer satisfaction of MARA with the service quality of MARA. The result find out that the most quality services dimensions that have high relationship with customer level satisfaction in MARA Melaka and MARA Muar is tangibles. The tangibles is appearance of physical facilities, equipment, personel and communication materials. The result also show that all of the dimensions of quality services have high relationship with customer services.